Measurement of isocenter alignment accuracy and image distortion of an 0.35 T MR-Linac system. (16th October 2019) - Dorsch, S; Mann, P; Elter, A; Runz, A; Spindeldreier, C K; Klüter, S; Karger, C P
Abstract: For hybrid devices combining magnetic resonance (MR) imaging and a linac for radiation treatment, the isocenter accuracy as well as image distortions have to be checked. This study presents a new phantom to investigate MR-Linacs in a single measurement in terms of (i) isocentricity of the irradiation and (ii) alignment of the irradiation and imaging isocenter relative to each other using polymer dosimetry gel as well as (iii) 3-dimensional (3D) geometric MR image distortions. The evaluation of the irradiated gel was performed immediately after irradiation with the imaging component of the 0.35 T MR-Linac using a T2-weighted turbo spin-echo sequence. Eight plastic grid sheets within the phantom allow for measurement of geometric distortions in 3D by comparing the positions of the grid intersections (control points) within the MR-image with their nominal position obtained from a CT-scan. The distance of irradiation and imaging isocenter in 3D was found to be (0.8  ±  0.9) mm for measurements with 32 image acquisitions. The mean distortion over the whole phantom was (0.60  ±  0.28) mm and 99.8% of the evaluated control points had distortions below 1.5 mm. These geometrical uncertainties have to be considered by additional safety margins.